Production objectives and market forces - Anteneh, A. (International Livestock Centre for Africa, 1982)
Discusses the advantages of small ruminant production in Africa, outlining their contribution to milk, meat & wool production; special attributes of small ruminants vis-a-vis larger stock in meeting production objectives, with particular reference to attributes such as small size, reproductive & marketing efficiency and adaptability. Describes the market situation for small ruminants & their products using the Middle East market for East African sheep & goats, and the demand for white wool in the Ethiopian carpet industry as examples.